1999
DOI: 10.1080/095530099139115
|View full text |Cite
|
Sign up to set email alerts
|

Increased exposure to pollutant aerosols under high voltage power lines

Abstract: The observations demonstrate a mode of increased exposure to pollutant aerosols under high voltage power lines by increased deposition on the body. The total (indoor + outdoor) 218Po and 214Po dose to the basal layer of facial skin is estimated to be increased by between 1.2 and 2.0 for 10% of time spent outdoors under high voltage power lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Atmospheric electric fields have been reported to cause behavioural changes in insects (Edwards, 1960a;Maw, 1962) and static electric fields up to 20 kV m -1 can be generated by equipment such as televisions. Underneath high voltage power lines, static electric fields can reach 11 kV m -1 at ground level and far higher at closer proximity to the power line (Fews et al, 1999a;Fews et al, 1999b). The results of the present study showed that avoidance and behavioural changes occurred in free-moving cockroaches confronted with static electric fields of 8 kV m -1 and above.…”
Section: Discussionmentioning
confidence: 47%
“…Atmospheric electric fields have been reported to cause behavioural changes in insects (Edwards, 1960a;Maw, 1962) and static electric fields up to 20 kV m -1 can be generated by equipment such as televisions. Underneath high voltage power lines, static electric fields can reach 11 kV m -1 at ground level and far higher at closer proximity to the power line (Fews et al, 1999a;Fews et al, 1999b). The results of the present study showed that avoidance and behavioural changes occurred in free-moving cockroaches confronted with static electric fields of 8 kV m -1 and above.…”
Section: Discussionmentioning
confidence: 47%
“…It was also argued that electromagnetic frequencies could produce negative health effects (Jayne, 2008). This was confirmed by Fews et al (1999) who demonstrated an increased deposition of harmful aerosols under 400kv and 275kv lines. Debrezion et al (2006) found a negative effect of distance to railways on property values, which they say is probably due to noise effects.…”
mentioning
confidence: 60%
“…A significant portion of these electrons is lost to the surrounding air as negative air ions. The amount lost will be amplified where sharp conductors are present, including dirt that has accumulated on the line, or pits in the line [Fews et al, 1999a].…”
Section: Discussionmentioning
confidence: 99%